2018
DOI: 10.1080/09540105.2018.1515893
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of Bisphenol A based on an aptasensor with DNA amplification

Abstract: An ultrasensitive and selective method for Bisphenol A (BPA) detection using aptamer-BPA and real-time quantitative polymerase chain reaction (RT-qPCR) technology is reported, in which biotin-modified aptamer DNA (BPA) is fixed on the inner wall of a streptavidin-coated PCR tube via biotin-avidin interactions and the template is fixed through the complementary base pairing with aptamer DNA. Upon the addition of BPA, the template DNA could be off from the inner wall of PCR tube, which results from aptamer DNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Bisphenol A (BPA) is mainly used for the production of polycarbonate plastics and epoxy resins, which are widely applied in the manufacturing of food contact materials, such as water pipes, plastic (milk) bottles, and food and drink (milk powder) packaging/cans . It has been reported that BPA can interfere with the basic physiological processes and cause various disorders, including metabolic disease, thyroid dysfunction, neurological defects, and cancer. , In many countries, the use of BPA in plastic infant feeding bottles is prohibited .…”
Section: Application Of Fluorescent Aptasensor For the Detection Of F...mentioning
confidence: 99%
“…Bisphenol A (BPA) is mainly used for the production of polycarbonate plastics and epoxy resins, which are widely applied in the manufacturing of food contact materials, such as water pipes, plastic (milk) bottles, and food and drink (milk powder) packaging/cans . It has been reported that BPA can interfere with the basic physiological processes and cause various disorders, including metabolic disease, thyroid dysfunction, neurological defects, and cancer. , In many countries, the use of BPA in plastic infant feeding bottles is prohibited .…”
Section: Application Of Fluorescent Aptasensor For the Detection Of F...mentioning
confidence: 99%